Dampak Keberadaan Tempat Pemrosesan Akhir Blang Bintang Terhadap Kondisi Lingkungan - Ahmad Nubli Gadeng; Raudhatul Firda; Daska Azis; Ruliani (Program Studi Pendidikan IPS Unesa, 2026)
The purpose of this study was to determine the impact of the existence of the Blang Bintang final processing site on environmental conditions. A qualitative approach with a descriptive type was used in this study. Data collection techniques used observations at the landfill site and interviews with informants of the landfill management and the community who are active around the Blang Bintang landfill. The research location was the Blang Bintang landfill, Aceh Besar Regency. Data analysis techniques used were data reduction, data display and drawing conclusions or verification. The results of the study showed that the final processing site is a place where waste is safely isolated so as not to cause disturbances to the surrounding environment. The Blang Bintang landfill is a new landfill built after the tsunami as an urgent need for waste storage and a replacement for the old landfill in Gampong Jawa, Banda Aceh City, which was damaged and full. Then, the impacts caused to the environment by landfill activities such as the impact of water, air and soil pollution are still relatively low, however, the potential for pollution remains, especially surface water pollution such as reservoirs and rivers that occurs during the rainy season.